Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.